(untitled) (Bangladesh Journal of Medical Science, 2020)
Cardiac arrest is the leading cause of death globally, and heart disease is known to be a major risk factor for cardiac arrest. In practice, an arrest is presumed to be of cardiac origin unless it is known or likely due to non-cardiac causes. The prognosis of the patient following cardiac arrest is generally poor. Although thrombolytic therapy is well known to be the treatment for myocardial thrombosis, it is not routinely recommended in cardiac arrest due to its potential bleeding adverse effect. We described a case report of successful thrombolytic therapy in cardiac arrest patient Bangladesh Journal of Medical Science Vol.19(2) 2020 p.319-321